2015
DOI: 10.1016/j.jns.2015.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Charcot–Marie–Tooth disease gene ARHGEF10 with paclitaxel induced peripheral neuropathy in NCCTG N08CA (Alliance)

Abstract: The predisposition of patients to develop polyneuropathy in response to toxic exposure may have a genetic basis. The previous study Alliance N08C1 found an association of the Charcot-Marie-Tooth disease (CMT) gene ARHGEF10 with paclitaxel chemotherapy induced peripheral neuropathy (CIPN) related to the three non-synonymous, recurrent single nucleotide variants (SNV), whereby rs9657362 had the strongest effect, and rs2294039 and rs17683288 contributed only weakly. In the present report, Alliance N08CA was chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
1
36
1
Order By: Relevance
“…We did not find low frequency variants in PRX and common variants in ARHGEF10 associated with paclitaxel-induced neuropathy, although the 2 nd and 3 rd top protective genes were these two, similarly to Beutler et al For the ARHGEF10 common variant rs9657362 we also found a trend towards protection (20,45). We also observed a trend towards increased neuropathy risk for other CMT genes (SEPT9 and SH3TC2).…”
Section: Concerning Other Genes Potentially Associated With the Neurosupporting
confidence: 85%
“…We did not find low frequency variants in PRX and common variants in ARHGEF10 associated with paclitaxel-induced neuropathy, although the 2 nd and 3 rd top protective genes were these two, similarly to Beutler et al For the ARHGEF10 common variant rs9657362 we also found a trend towards protection (20,45). We also observed a trend towards increased neuropathy risk for other CMT genes (SEPT9 and SH3TC2).…”
Section: Concerning Other Genes Potentially Associated With the Neurosupporting
confidence: 85%
“…Next-gen genomic DNA sequencing associated Charcot-Marie-Tooth disease (hereditary neuropathy) related genes to CIPN in the N08C1 study [50]. Importantly, key results could be retested in N08CA, in which the same PRO-based CIPN phenotyping had been performed, validating the lead finding [51]. A literature review on taxane-associated neuropathy single nucleotide polymorphisms (SNPs) was conducted, and then a validation study was conducted in samples from the N08C1 paclitaxel neuropathy natural history trial; a manuscript describing these findings is currently under review (Beutler, personal communication, October 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Basic science studies of genetic predisposition to toxic effects and pharmacogenetics are needed. Achievements to date include an understanding of the genomic basis for aromatase-associated arthralgias 189,190 and associated chemotherapy-induced peripheral neuropathy. 191 Additional funding is needed for translational studies that bridge laboratory data to treatment in the clinic and home and for clinical trials to investigate drug mechanisms and evaluate potential therapies in patients.…”
Section: Supportive Carementioning
confidence: 99%